Special Recommendations for Preparation of Students in Schools and Family Cooperation - Muhayo Botiralevna, Artikova (International Journal of Psychosocial Rehabilitation, 2020)
The article outlines the importance of preparing students for entrepreneurship, identifying its developmental factors, and addressing the challenges that need to be addressed through school and family partnerships. As a result of the research, recommendations will be made to increase the interest of students in business and entrepreneurship education, to create a motivational and motivating environment, and to enhance the effectiveness of entrepreneurial competence.